sGC Activity and Regulation of Blood Flow in a Zebrafish Model System - Vishnolia, Krishan K.; Rakovic, Aleksandar; Hoene, Celine; Tarhbalouti, Karim; Aherrahrou, Zouhair; Erdmann, Jeanette (Frontiers in Physiology, 2021)
Soluble guanylyl cyclase (sGC) protein is a heterodimer formed by two subunits encoded by the GUCY1A1 and GUCY1B1 genes. The chromosomal locus 4q32.1 harbours both of these genes, which has been previously significantly associated with coronary artery disease, myocardial infarction, and high blood pressure. Blood pressure is influenced by both the environment and genetics and complemented by several biological pathways. The underlying mechanisms associated with this locus and its genes still need to be investigated. In the current study, we aimed to establish the zebrafish as a model organism to investigate the mechanisms surrounding sGC activity and blood pressure. A zebrafish mutant gucy1a1 line was generated using the CRISPR-Cas9 system by inducing a 4-bp deletion frameshift mutation. This mutation resulted in a reduction of gucy1a1 expression in both heterozygote and homozygote zebrafish. Blood flow parameters (blood flow, arterial pulse, linear velocity, and vessel diameter) investigated in the gucy1a1 mutants showed a significant increase in blood flow and linear velocity, which was augmented in the homozygotes. No significant differences were observed for the blood flow parameters measured from larvae with individual morpholino downregulation of gucy1a1 and gucy1b1, but an increased blood flow and linear velocity was observed after co- morpholino downregulation of both genes. In addition, the pharmacological sGC stimulator BAY41-2272, rescued the impaired cGMP production in the zebrafish gucy1a1+/- mutant larvae. Downregulation of cct7 gene did not show any significant difference on the blood flow parameters in both wildtype and gucy1a1+/- background larvae. In summary, we successfully established a zebrafish platform for investigating sGC-associated pathways and underlying mechanisms in depth. This model system will have further applications, including for potential drug screening experiments.